Cardioprotective Roles of β-Hydroxybutyrate Against Doxorubicin Induced Cardiotoxicity - Liu, Yihai; Wei, Xuan; Wu, Mingyue; Xu, Jiamin; Xu, Biao; Kang, Lina (Frontiers in Pharmacology, 2021)
Background: β-Hydroxybutyrate (BHB) is produced by fatty acid oxidation in the liver under the fasting state and confirmed to play a cardioprotective role in ischemia and hypertensive settings. Doxorubicin (DOX) is an effective chemotherapeutic drug, but limited by serious irreversible cardiotoxicity. However, whether BHB can protect from DOX-induced cardiotoxicity remains unknown. Methods and Results: C57BL/6 mice were intraperitoneally injected with DOX to induce cardiac toxicity and intragastrically administered into BHB for treatment. They were randomly divided into three groups, namely a sham group (Sham), a doxorubicin group (DOX), and a doxorubicin+β-Hydroxybutyrate group (DOX+BHB). Echocardiography and pathological staining were performed to evaluate cardiac function and fibrosis. H9c2 cardiomyocyte was treated with DOX or BHB for in vitro experiments. Cell apoptosis and ROS were determined by flow cytometry. BHB significantly restored DOX-induced cardiac function decline and partially prevented cardiac reverse remodeling, characterized by increased cell size and decreased fibrosis. In vitro, BHB treatment decreased cellular injury and apoptosis. Also, BHB alleviated oxidative stress level and increased mitochondrial membrane potential. Conclusion: Our results suggested that BHB could protected from DOX-induced cardiotoxicity by inhibiting cell apoptosis and oxidative stress and maintaining mitochondrial membrane integrity.